Cannabinoid synthases and osmoprotective metabolites accumulate in the exudates of Cannabis sativa L. glandular trichomes - Rodziewicz, Paweł (Plant science : an international journal of experimental plant biology, 2019)
Copyright © 2019 Elsevier B.V. All rights reserved.